2013
DOI: 10.2478/frp-2013-0018
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic features of Fraxinus excelsior L. with wavy-grained wood growing in Ukraine

Abstract: Abstract. The paper presents analysis of biometric features of ash with wavy-grained wood, which has decorative appeal. The research results shows that fresh broadleaves ash forest stands growing in the Vinnytsya and Sokyryany Regions of Ukraine have high potential for growing curly ash. The differences between straight-grained and wavygrained wood density and macrostructure were analysed and estimated. Statistical evaluation of the aesthetic macrostructure of wood characteristics indicated that the length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Hejnowicz and Romberger (1973) showed that in ash for example, the waves were not apparent before 10 years. This was recently confirmed by Sopushynskyy and Teischinger (2013). Such a wavy grain formation can be observed in a minor number of trees within a population in almost all deciduous trees.…”
Section: Wood Structuresupporting
confidence: 63%
“…Hejnowicz and Romberger (1973) showed that in ash for example, the waves were not apparent before 10 years. This was recently confirmed by Sopushynskyy and Teischinger (2013). Such a wavy grain formation can be observed in a minor number of trees within a population in almost all deciduous trees.…”
Section: Wood Structuresupporting
confidence: 63%
“…Green ash has an air dry density of 702 kg/m 3 , it is almost 10% higher than those mentioned by Meier (2015), while having nearly the same basic density. The test results correspond to the density of the common ash (Wagenführ 2007, Sopushynskyy and Teischinger 2013, Meier 2015, Diler 2017, Giagli et al 2018, making the wood characteristics very similar.…”
Section: Resultsmentioning
confidence: 68%
“…Analysing the investigations of domestic and foreign researchers, we established that the most important factors contributing to the successful growth and distribution of stands with ash trees in the composition are soil and hydrological conditions. As a rule, ash stands grow in lower relief areas on fresh and moist mineral-rich and well-drained soils (Marigo et al, 2000;Dobrowolska et al, 2011;Sopushynskyy, 2012). River floodplains also create favorable conditions for the regeneration of common ash (Dufour & Piegay, 2008).…”
Section: Discussionmentioning
confidence: 99%